Carbon foot print evaluation in tunneling construction using conventional methods. (February 2021) - Rodríguez, Rafael; Pérez, Fernando
Highlights: A CO2 calculation model is proposed, calibrated and used with different tunnels. Emissions rates in kgCO2 /m for tunnels under different conditions are given. Main CO2 emission is related to manufacturing of concrete for the support/lining. RMR and cross section (S) are the main tunnel parameters affecting CO2 emissions. Abstract: The construction sector is one of the most relevant related to the emissions of the greenhouse gases (GHG). Within this sector, the weight of tunneling construction is significant considering the resources employed (for example, tunnel construction represents about the 25% of the total concrete used in civil works in Spain). Nevertheless, it seems that there is still a gap to make the calculations of these emissions for each specific tunnel during its design and later during its construction, taking into consideration the specific parameters that influence them. The present work provides the fundamentals for applying in a simplified way the Life Cycle Assessment method (LCA). A simplified calculation model is propose to estimate the CO2 emissions of each step of the construction phase in the case of tunnels advanced through medium to low strength rockmass by conventional methods (drilling and blasting, roadheader or hydraulic breaker hammer). The CO2 emissions can be calculated by estimating the amount of diesel, electrical energy and materials consumed, and then using the conversion factors to CO2, from well recognized organizations or more domestic sources (as some Spanish institutions). The simplified calculation model has been tested with data of a real tunnel and then it is used to analyze CO2 emissions of different tunnels to determine the influence of different factors. The main conclusion is that, for this kind of tunnels, the most relevant contribution to CO2 emissions is that associated to the fabrication of concrete used in the support and lining of the tunnel which represents, in average, about 80% of the total.